Leadership Practice in Sport and Exercise Medicine – from diagnosis to dialogue - Philip Glasgow (International Journal of Sports Physical Therapy)
Leadership advice is everywhere. Across social media platforms, in formal teaching environments, and a large number of industries we are bombarded with courses, podcasts, books, and conferences telling us how to be a great leader. But what does it mean to lead well in sport and exercise medicine? How can we demonstrate leadership in inter-disciplinary teams to support athlete performance and promote wellbeing? What skills are required to lead complex discussions on athlete availability?